AL-ALBĀNĪ METHODOLOGY IN DETERMINING THE FAITH OF HADITH: STUDY OF THE BOOK OF IRWĀ AL-GALĪL FĪ MANĀR AL-SABĪL BY AL-ALBĀNĪ - Muhammad Rafiâ€™iy Rahim,; Arifuddin Ahmad,; Darsul S Puyu,; La Ode Ismail Ahmad, (Jurnal Adabiyah, 2022)
Muhammad Nāṣir al-Dīn al-Albānī is one of the most controversial contemporary hadith scholars of this century. He has attracted many researchers to explore his life and works. This study aims to examine more deeply the methodology in determining the level of the dhaif of hadith (Study of the book of Irwā' al-Galīl fī Takhrīj Aḥādīṡ Manār al-Sabīl). Classifying the assessment of the quality of al-Albānī hadith in the book of Irwā al-Galīl fī Manār al-Sabīl. This research is qualitative in the form of literature (library research). Second, as for the classification of hadith in Irwā' al-Galīl fī Takhrīj Aḥādīṡ Manār al-Sabīl there are 5 types of groups including 1) types of validity; 2) type of Hasan; 3) type of dhaif; 4) type of maudhu'; 5) the type of hadith that has no status or certainty. As for the types of hadith validity, there are 26 kinds of assessments where the total number of hadiths is 1726. There are 6 types of hasan assessment with 205 the number of hadith as many as 174 hadith. There are 26 types of ta'afan assessments with a total of 501 hadiths. Maudhu' types are 3 types of assessment terms with a total of 14 hadiths, while the types of hadiths that do not have certainty or status are 163 hadiths. الملخص يعتبر محمد ناصر الدين الألباني من أكثر علماء الحديث المعاصرين إثارة للجدل في هذا القرن. لقد استقطب العديد من الباحثين لاستكشاف حياته وأعماله. تهدف هذه الدراسة إلى التعمق في المنهجية في تحديد مستوى ضيف الحديث (دراسة كتاب إرواء الغليل في تخريج آحاديث منار السبيل). - تصنيف تقييم صفة حديث الألباني في كتاب إرواء الغليل في منار السبل. هذا البحث نوعي في شكل مؤلفات (بحث مكتبة). ثانياً: بالنسبة لتصنيف الحديث في إرواء الغليل في تخريج آحاديث منار السبل ، هناك 5 أنواع من المجموعات ، منها 1) أنواع صدق. 2) نوع الحسن. 3) نوع الضيف. 4) نوع المودة. 5) نوع الحديث الذي ليس له صفة أو يقين. أما بالنسبة لأنواع الأحاديث النبوية ، فهناك 26 نوعًا من التقويمات حيث يبلغ إجمالي عدد الأحاديث 1726. وهناك 6 أنواع من الأحاديث النبوية ، وعددها 205 أحاديث يصل عددها إلى 174 حديثًا. يوجد 26 نوعًا من تقييمات التعافين بإجمالي 501 حديثًا. أنواع المودة هي ثلاثة أنواع من مصطلحات التقييم بإجمالي 14 حديثًا ، في حين أن أنواع الأحاديث التي ليس لها يقين أو حالة هي 163 حديثًا.